An Analysis of Flasback Plot in the Inception Movie - Puspitasari, Ni Putu Riana (ID Solutions, 2024)
This study is entitled “An Analysis of flashback plot in the Inception Movie.” Movie Inception by Christopher Nolan as the objects of the research. The aims of this study were (1) to describe the plot arrangement of the Inception movie and (2) to describe the type of the plot in the Inception movie. This study used the theory proposed by Holman (1980) to conduct this study. Descriptive and qualitative method were used in this study, in order to collect the data. Such as downloading the movie from the internet, watching and listening to the movie throughly, classifying various fragments of sentences, dialogues, and scenes. Then, examine, analyze, and interpret these fragments in order to understand the plot structure according to the theory. The results reveal that the plot structure of